Movement analysis in Rhythmic Gymnastics using a full body inertial measurement system - Wolfsperger, F.; Hökelmann, A. (World Congress of Performance Analysis of Sport VIII, 2008)
While trying a multiple person capturing with two gymnasts the wireless (bluetooth) data transmission didn`t work correctly. Due to the transmission unit, located on the back of the suit, some exercises couldn`t be done. The uncomplicated calibration process, standing in T-pose for few seconds, was completed by input of body and foot length. For more accuracy further body segment lengths can be added as well as extra calibration poses. So far, the process of data collection is tremendously easier compared to a 3d video metric analysis. Capturing fast movements, the body segments in the 3d animation video loses connection to each other, indicating a loss of accuracy in the global position data, which are calculated by double integration of body segment accelerations (Xsens, 2008). Deductive, for further calculations like joint angles, it is recommended to use the orientation data and quaternion arithmetic instead of vector geometric calculations with global position data. Fig. 2a also shows the left knee angle calculated with position data, differing up to 14° to the angle calculated with orientation data. This full body IMS shows advantages concerning data acquisition and 3d analysis of complex movements. Though in this almost static case the measurements accuracy seems acceptable. But it has to be evaluated in further studies, especially for dynamic cases. Besides affecting the athletes performance by weight and location of the technical equipment, it must be considered, that damages to that on-body-system are quiet possible and lead to additional costs.